Evaluation of the predictive value of CHA2DS2-VASc Score for no-reflow phenomenon in patients with ST-segment elevation myocardial infarction who underwent Primary Percutaneous Coronary Intervention - Abd El-Moneum, Mahmoud Shawky (Journal of Cardiology and Cardiovascular Medicine, 2019)
Objective: The aim of this study was to estimate the predictive clinical value of CHA2DS2-VASc score for no-reflow phenomena in patients having ST-segment elevation myocardial infarction (STEMI) who applied to primary percutaneous coronary intervention (PCI). Subjects and Methods: Three-hundred STEMI patients underwent primary PCI. They were classified into: group (1) included 27 patients with no-reflow and group (2) included 273 patients without no-reflow (control). CHA2DS2-VASc risk score was computed for each patient. Results: This study found statistically significant difference (p < 0.05) in multivariate analysis of the association between CHA2DS2-VASc score and no-reflow phenomenon. The predictive power of individual components in CHA2DS2-VASc score for no-reflow was statistically significant difference (p < 0.05). So, significantly higher CHA2DS2-VASc score is connected with higher risk of no-reflow and in-hospital mortality rate. Conclusion: Significantly higher CHA2DS2-VASc score is associated with higher risk of no- reflow phenomenon and in-hospital mortality rates in patients with STEMI who underwent primary PCI.